Teachers’ Strategies for Implementing Outdoor Learning with Children Aged 5–6 Years - Aprilia, Bella Rahmanda; Afifah, Sofia Nur; Alfina, Alisa (Kiddie: Early Childhood Education and Care Journal, 2026)
Studies on outdoor learning in early childhood education have largely focused on its general benefits and contribution to children’s development, while studies specifically examining teachers’ operational strategies in implementing such activities in the field remain limited. This study aims to describe and analyze teachers’ strategies in implementing outdoor learning for children aged 5-6 years at TK Islam Masyithoh, Madiun City. This study used a qualitative approach with a descriptive qualitative design. The informants consisted of one classroom teacher of group B2 and one school principal as primary data sources, along with the students of group B2 as the subjects of observation; all were selected due to their direct involvement in the implementation of outdoor learning. Data were collected through participatory observation, in-depth interviews, and documentation, with data validity tested through source and technique triangulation, and analyzed using the Miles and Huberman interactive model. The results showed that teachers’ strategies in implementing outdoor learning consisted of seven interrelated forms: managing children’s arrival, managing the environment and learning media, providing initial instructions, accompanying children during practice, managing tools and materials, managing transitions between activities, and managing the closing of the activity. These seven strategies predominantly reflected the application of experiential learning, as seen in children’s direct involvement in a pizza-making cooking class. These findings reinforce the understanding that the success of outdoor learning in early childhood is determined not only by planning, but also by teachers’ ability to manage the entire sequence of activities systematically, from children’s arrival to their departure.